PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING: (Studi Pada Konsumen Mixue di Daerah Istimewa Yogyakarta) - Nur Najmi; Krisna Mutiara Wati (Ekomania, 2024)
This study is to determine the effect of customer relationship management on customer loyalty with customer satisfaction as an intervening variable (study on mixue consumers in Special Region of Yogyakarta). With many Mixue outlets spread across the Special Region of Yogyakarta. Hopefully, it can maintain relationships with their customers. In this case Mixue must be able to build and maintain customer relationships well and profitably. As well as creating and maintaining customer loyalty. This type of quantitative research with purposive sampling method and a sample size of 100 respondents distributed via google form. Data analysis using smartPLS software version 4.0. It is concluded that customer relationship management has a significant influence on customer satisfaction, and customer satisfaction plays a good role as a mediating influence of customer relationship management on customer loyalty. However, there is no influence between customer relationship management on customer loyalty.